Reengaging in Agricultural Water Management: Challenges and Options - World Bank (Washington, DC: World Bank, 2012)
The overall goal of this report is to give strategic focus to implementation of the agricultural water management (AWM) components of the corporate strategies. Its specific objectives are to set out the changing context of demand and supply for agricultural water; to identify the policy, institutional, and incentive reform options that will accelerate productivity improvements and pro-poor growth; and to articulate priorities for investment in AWM. It is also intended to define the role of the public sector and other stakeholders, and to set out how AWM can be best integrated upstream into water resources management, and downstream as an input provider into the agricultural economy.